Pengaruh Model Project Based Learning (PJBL) Terhadap Hasil Belajar Keliling Dan Luas Bangun Datar Kelas IV SD - Lisa Ariani; Melva Zainil (Universitas Negeri Padang, 2020)
This study aims to determine the effect of the Project Based Learning (PjBL) model on student learning outcomes in the circumference and wide flat area in grade IV Elementary School. This type of research is Quasi Experimental. The sampling technique uses purposive sampling. The instrument used was an objective test. Based on the calculation results of the analysis, t-test with a significance level of 0.05 obtained t-count (1.69) and t-table (1.66). So that the t-count ˃ t-table, where 1.69 ˃ 1.66. Ha accepted, it can be concluded that there is an influence of the use of the PjBL model on learning outcomes in the traveling material and flat area of the fourth grade students of SDN Gugus II, Lubuk Kilangan Padang.